The Impact of Local Culture on Financial Performance in Property Firms in Bali - Astawa, I Putu; Sudika, Putu (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
The research studies local culture reflected through pray, hard work, honesty, tatwamasi and gotong royong influencing property sales and company assets. Fifty companies are qualified as sample of sixty one property companies actively operated in 2013. Data is collected through questionnaire having tested for its reliability and validity before distributed to those fifty companies. The collected data is analyzed with multipleÂ regression. Result shows that hard work, honesty, tatwamasi and gotong royong culture that well implemented are able to improve property sale and assets ownership. Result of the study has implication that in order to improve financial performance, local culture should be included as variable in performance measurement. Result of the study gives contribution to Scheinâ€™s organizational culture (2004) that colored with local culture; therefore, values believed in an organization are able to improve performance.